E-voting jako alternatywna procedura glosowania na przykładzie Estonii – szanse i zagrożenia - Dyś-Branicka, Iwona (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
Electronic voting, also known as a e-voting, in general consists of two main types: voting with the electronic voting machines located at polling station and remote e-voting via Internet. The second type is an example of alternative voting procedures. It enables voters to vote via computers, using the Internet so that they do not have to go to the polling station anymore. In that way, e-voting provides improved accessibility not only for disabled voters, but for anyone who want to vote from home. What is more, it is easier and faster to count votes by the electronic system than manually. On the other hand, opponents of e-voting emphasise the disadvantages of this alternative procedures. First of all, they underline that it is expensive to introduce. Then, it can causes the electoral fraud and what is more important, it does not guarantee proper level of security. Estonia is one of the European country which decided to mandate electronic voting. It is available for all citizens. In Poland, for several years this issue has been under public discussion. The author of this article tries to analyse the influence of electronic voting on voter turnout. Basing on the analisis, the author makes a conclusion that unfortunately implementation of alternative voting procedures is not enough to increase the voter turnout. On the other hand, electronic voting is compliant with constitutional rules and it facilitates the access to democratic procedures.
Keywords: ballot; voter turnout; alternative voting procedures; election laws; electronic voting; Estonia; universal suffrage; direct suffrage